2022
DOI: 10.37284/eajhs.5.2.995
|View full text |Cite
|
Sign up to set email alerts
|

Enablers and Barriers to Chlorhexidine Use in Umbilical Cord Care: Voices of Care Givers and Healthcare Providers in Selected Counties in Kenya

Abstract: Neonatal sepsis contributes to increased rates of mortality among newborns during their first month of life. Chlorhexidine (CHX) has proven effective in the prevention of neonatal sepsis due to umbilical stump infection after birth. Despite shifting from dry cord care techniques to CHX use, there is still a high prevalence of improper cord care in low-resource settings in Kenya. This study sought to explore barriers and enablers to CHX use in Kwale, Vihiga and Machakos counties in Kenya. We adopted mixed metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“… 28 A 2022 study in Kenya revealed that only 1.3% used chlorhexidine gel for cord care, which is a much lower percentage compared with the current study. 30 The findings of this study revealed that parity of the women was not significantly associated with utilisation of chlorhexidine gel (p=0.736). The utilisation was almost the same for different parities.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“… 28 A 2022 study in Kenya revealed that only 1.3% used chlorhexidine gel for cord care, which is a much lower percentage compared with the current study. 30 The findings of this study revealed that parity of the women was not significantly associated with utilisation of chlorhexidine gel (p=0.736). The utilisation was almost the same for different parities.…”
Section: Discussionmentioning
confidence: 58%
“…In a similar study among healthcare providers, it was reported that with the application of chlorhexidine gel to the umbilical stump, the cord takes longer to heal because it leaves the cord wet, which delays the healing process, and that they prefer to use the spirit. 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study conducted in Kenya found that cultural beliefs and taboos were barriers to the implementation of chlorhexidine use for cord care. 23 In the African context, diverse cultural beliefs exist regarding cord care practices. Strategies to overcome negative beliefs especially in culturally endowed communities like Kenya, regarding cord care should be explored.…”
Section: Discussionmentioning
confidence: 99%